2022
DOI: 10.3390/ani12192660
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Genetic Analyses of Melanistic Iguanas Highlight the Need to Monitor the Iguanid Trade

Abstract: Lizards within the Iguana iguana species complex are among the most common reptilian pets, with the widest natural geographic range among iguanids. Deep phylogenetic divergence distinguishes multiple mitochondrial clades, and several taxonomic changes have recently been proposed. These small populations, typically island endemics, are threatened by numerous factors, including the international pet trade. Recent investigations reveal the absence of required CITES permits for lawful export of animals, providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Eventhough a complete overview is still lacking, scalation and coloration patterns have already been found to be highly variable throughout the I. iguana complex. We assessed the presence of enlarged nasal scales and a melanistic facial patch in both the Saba and Montserrat population, given previous morphological assessments of these populations (Breuil et al, 2020;van den Burg et al, 2022). Among both populations, only three Saba animals had enlarged nasal scales (horn) and were additionally assigned as non-native by microsatellite and sequence data.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Eventhough a complete overview is still lacking, scalation and coloration patterns have already been found to be highly variable throughout the I. iguana complex. We assessed the presence of enlarged nasal scales and a melanistic facial patch in both the Saba and Montserrat population, given previous morphological assessments of these populations (Breuil et al, 2020;van den Burg et al, 2022). Among both populations, only three Saba animals had enlarged nasal scales (horn) and were additionally assigned as non-native by microsatellite and sequence data.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid and non-native iguanas are believed to be more territorially aggressive and have higher reproductive fitness thanks to larger clutch sizes compared with I. delicatissima (van Wagensveld & van den Burg, 2018). Although data on the clutch size from the Montserrat and Saba populations are practically unavailable (Blankenship, 1990;van den Burg et al, 2022), insular Iguana populations have generally been found to have smaller clutch sizes than continental populations (e.g., Fitch & Henderson, 1977;van Marken Lichtenbelt & Albers, 1993;Bock et al, 2018), even though this is believed to be partially climate dependent (e.g., Novosolov, Raia, & Meiri, 2013). The available data suggest that the Montserrat and Saba populations produce clutch sizes within the lower range recorded for I. iguana, potentially allowing reproductive and genetic swamping when non-native or hybrid iguanas would reproduce within these island populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations